Diagnostic value of serum brain-derived neurotrophic factor (BDNF), neuronspecific enolase (NSE), glial fibrillary acidic protein (GFAP), plasma viscosity (PV) as well as fibrinogen (FIB) in acute cerebral infarction patients: Diagnostic value of serum brain-derived neurotrophic factor (BDNF), neuronspecific enolase (NSE), glial fibrillary acidic protein (GFAP), plasma viscosity (PV) as well as fibrinogen (FIB) - Wang, Fei (Journal of Medical Biochemistry, 2025)
Objective: To explore the Diagnostic value of serum brain-derived neurotrophic factor (BDNF), neuronspecific enolase (NSE), glial fibrillary acidic protein (GFAP), plasma viscosity (PV) as well as fibrinogen (FIB) in patients receiving butylphthalide and sodium chloride injection in combination with atorvastatin calcium in acute cerebral infarction patients. Methods: Eighty ACI patients accepted therapy in our hospital from January 2022 to January 2024 were included to be study objects, followed by dividing into control group (CG) and study group (SG). The CG was given atorvastatin calcium tablets. On the basis of the CG, the SG accepted butylphthalide and sodium chloride injection. The clinical efficacy, neurological impairment, activity of daily living ability, hemorheological indicators, neurobiochemical indicators, and occurrence of adverse reactions in 2 groups were compared. Results: Relative to the CG, the total effective clinical effect rate in the SG presented elevation (P<0.05). After therapy, the NIHSS score in the SG presented reduction relative to the CG, BI score in the SG presented higher relative to the CG (P<0.05), the whole blood high shear viscosity, whole blood low shear viscosity, PV, HCT as well as FIB levels in the SG presented reduction relative to the CG (P<0.05), the improvements of BDNF, NSE and GFAP levels in the SG were superior to the CG (P<0.05), and the occurrence of adverse reactions between 2 groups was no significant (P>0.05). Conclusion: Butylphthalide sodium chloride injection in combination with atorvastatin calcium tablets can improve the total therapeutic response rate, improve neurological impairment, promote patients’ daily life ability, improve cerebral hemodynamics and neurobiochemical indexes in the therapy of ACI patients, which is worthy for clinical promotion.